Exploration of the Microscopic Pore Structure of Unconventional Energy Resource using Electrodeposition. (February 2019) - Xu, Jin; Jianming, Li; Xiaoqi, Wang; He, Liu; Xiaodan, Liu
Abstract: The microscopic pore structure of unconventional petroleum reservoirs, such as shale gas、 tight oil、tight gas, and so on, namely the size, geometry, distribution, and interconnected relations of the pores and throats of a shale rock, directly affects their porosity, storage, and permeability. Studies related to the microscopic pore structure of shale are considered to be attractive to evaluate the shale resource and to elucidate their distribution law; additionally, studies aim to improve the productivity and recovery ratio of both oil and gas. Therefore, methods that can be used to accurately characterize the microscopic pore structure of shale have received considerable attention. In this study, we combine electrochemical deposition and scanning electrode microscopy to characterize the microscopic pore structure of shale. Therefore, we could directly observe the three-dimensional microstructure of shale that are smaller than 50 nm with a large observing area. Additionally, the surface areas of the connected pores and throats of the shale are calculated.